QUALITY OF ALFALFA SEEDS FROM DIFFERENT REGIONS OF SERBIA DURING STORAGE UP TO 42 MONTHS - Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2024)
This study presents the findings from assessing the quality of alfalfa seeds collected from three Serbian regions: in each region, batches of seeds from six places were analyzed. The following criteria were investigated: the proportion of dormant seeds, the germinated seed content, the proportion of dead seeds, and the percentage of aberrant seedlings. Seed quality was assessed after six, eighteen, thirty, and forty-two months of storage. The highest seed quality was obtained after thirty and eighteen months of seed storage (91% and 89% of germination, respectively). During the 42-month storage period, the percentage of dead seeds (8%) and abnormal seedlings (7%) increased, while germination declined to 84%. In a storage period of six months, the participation of dormant seeds of 21% affected the germination rate, which was 77%, regardless of the low proportion of dead seeds (1%) and abnormal seedlings (2%).
Keywords: alfalfa, quality, seed, storage